IDDF2020-ABS-0057 Risk of incident hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) virus-infected patients treated with tenofovir disoproxil fumarate (TDF) versus entecavir (ETV): a US administrative claims analysis. (18th November 2020) - Kim, Ray; Telep, Laura; Lu, Mei; Ramroth, Heribert; Flaherty, John; Gaggar, Anuj; Chokkalingam, Anand; Kwan Chan, Carol Yee; Gordon, Stuart
Abstract : Background: TDF and ETV are first-line treatments for CHB virus infection. A recent analysis of nationwide insurance data from Korea suggested that the risk of HCC may vary by type of CHB treatment; however, this finding was based on a limited follow-up period following TDF approval in Korea in 2012 and has not been replicated in large datasets outside of Asia. The objective of this analysis was to explore the long-term risk of HCC with TDF vs. ETV in treatment naïve (TN) CHB patients in a US administrative claims dataset. Methods: Among 158, 272 patients with evidence of CHB and administrative medical claims between January 2006 and September 2018, we identified TN patients exposed to TDF (N=6, 145) or ETV (N=4, 046) with at least 1 year of continuous enrollment prior to cohort entry. Exclusion criteria included coinfection with HCV, HDV, or HIV; prior exposure to peginterferon or nucleos(t)ide analogues; HCC or liver transplant prior or up to 6 months after initiating treatment. Absolute rates and corresponding 95% CIs were determined for each treatment group, Cox proportional hazards methods were used to estimate the risk of incident HCC associated with TDF vs ETV. To account for the effects of potential differences in demographics and baseline health status, we incorporated multivariable adjustment and weighting based on treatment propensity scores. Results: Median follow-up duration was comparable in TDF- vs ETV-treated patients among TDF-treated CHB patients, the absolute rate of HCC was approximately half that of patients treated with ETV (0.32 per 100 PY (CI: 0.23 – 0.43) vs 0.61 per 100 PY (CI: 0.45 – 0.80)). After adjustment for age group, sex, baseline health conditions and propensity score weighting, TDF remained associated with a significantly decreased risk of HCC compared to treatment with ETV (HR: 0.56, CI: 0.37 – 0.86). Conclusions: In this analysis of commercially insured, TN CHB patients in the US, the absolute rate of HCC was lower in those treated with TDF than with ETV. After adjustment, treatment with TDF remained associated with a significantly decreased long term risk of HCC, consistent with recent findings from Asia.